Nitrogen, Phosphorus, and Potassium Fertilization for Newly Established Tall Fescue - D. W. Sweeney; J. L. Moyer; J. K. Farney (Kansas Agricultural Experiment Station Research Reports, 2018)
Tall fescue is the major cool-season grass in southeastern Kansas. Perennial grass crops, as with annual row crops, rely on proper fertilization for optimum production; however, meadows and pastures are often under-fertilized and produce low quantities of low-quality forage. Even when new stands are established, this is often true. The objective of this study was to determine whether N, P, and K fertilization improves yields during the early years of a stand.
Keywords: Nitrogen; phosphorus; potassium; tall fescue